Literary Historiography and Costa Rican Indigenous Literature: Exclusion and Epistemic Violence from the Rhetoric of Modernity - Gómez Jiménez, Andrey (2021)
The purpose of this research is to analyze the indigenous as a literary category and its relationship with the national historiographic discourse. Its objective is to prove the exclusion processes that the different indigenous aesthetic-literary manifestations have experienced in Costa Rican historiography, considered as a socio-discursive practice with political, cultural and ideological implications. The sources used include: –an anthology, two literary historical documents, and a literary dictionary, from which it was possible to study the construction processes (theoretical and methodological) of these texts through Mignolo's decolonial theory and rhetoric of modernity. The main findings show that there is a correlation between the colonial matrix of power and the processes of exclusion found in the texts studied, which correspond to European epistemological parameters.